Screening level ecological risk assessment of abandoned metal mines using chemical and ecotoxicological lines of evidence. (June 2019) - Son, Jino; Kim, Jeong-Gyu; Hyun, Seunghun; Cho, Kijong
Abstract: In the present study, a screening level site-specific ecological risk assessment (ERA) was conducted on 10 abandoned metal mines in Korea to determine the ecological risk and prioritize the mines requiring further investigation. A cost-saving approach was adopted by combining both the chemical (ChemLoE) and the ecotoxicological (EcotoxLoE) lines of evidence for the evaluation of integrated risk (IR), rather than applying the full spectrum of Triad, including ecological LoE. The risk values for ChemLoE were derived by calculating the toxic pressure based on the total and 0.01 M CaCl2 extractable metal(loid) concentrations. The risk values for EcotoxLoE were based on the mortality and reproduction of the collembolan species Paronychiurus kimi in the mine soils. A response surface model with a central composite design (CCD) was constructed to standardize the effects of soil physicochemical properties (i.e., organic matter content, clay content, and soil pH) on the reproduction of P. kimi. The predicted number of offspring was used as a reference for the calculation of risk value for reproduction. The ChemLoE and EcotoxLoE values ranged from 0.34 to 1.00 and 0.12 to 0.49, respectively, in the surveyed mines. The contribution of the ChemLoE value to the IR was higher than that of the EcotoxLoE value for all mines. Overall, two of the 10 mines were classified as high-risk soils with high IR values (IR > 0.76), but large deviations were also observed between the LoEs in these mines, suggesting the need for further studies to confirm the potential risks. The future investigations of these mines should focus particularly on providing additional evidence to reduce the degree of uncertainty for risk assessment. Graphical abstract: Image 1 Highlights: Site-specific ERAs were conducted for 10 mines in Korea. Chemical and ecotoxicological lines of evidence were used to determine the integrated risk (IR). An alternative approach to replacing the reference soil in bioassay was proposed. IR value was used to prioritize the mines requiring further investigation. Three out of 10 mines were at high risk with an IR value greater than 0.75. Abstract : A screening level site-specific ecological risk assessment on 10 abandoned mines in Korea based on chemical and ecotoxicological lines of evidence.